Facies analysis and depositional environment of Gir Bir Formation, Northwestern Iraq - Al-Hajj, Mohammed A.; Al-Juboury, Ali; Al-Hadidy, Aboosh H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Upper Cretaceous successions of the Gir Bir Formation (Cenomanian-Early Turonian) were studied in 15 wells from northwestern Iraq. The formation is composed of recrystallized, partly dolomitized limestone with local silicification. Benthonic foraminifera (Miliolids, Alveolina, and Orbitolina), rudist and peloids are the main constituents. The studied succession has been affected by several diagenetic events such as; dolomitization, recrystallization, micritization, dissolution, compaction and silicification. Facies analysis revealed that seven microfacies subdivided into eleven submicrofacies could be distinguished, reflecting sedimentary environments including; deep shelf margin, slope/shoal, rudist buildups, back reef/shoal, and protected lagoon in a regressive shallowing-upward sequence. Lateral facies variation showed that reefal facies were commonly located in northwestern parts of the study area, whereas lagoonal facies existed in eastern and southeastern parts. Rimmed carbonate platform is the acceptable model for the Gir Bir Formation.
Keywords: Gir Bir Formation,Facies; rudistbuildups; rimmedplatform